Extended Spectrum β-Lactamase (ESBL) Producing Multidrug Resistant Gram-Negative Bacteria from Various Clinical Specimens of Patients Visiting a Tertiary Care Hospital (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The purpose of this study was to assess multidrug resistance and Extended Spectrum β-Lactamase (ESBL) production in Gram negative bacterial pathogens.Methods: The study included clinical specimens sent for routine culture and antibiotic susceptibility testing. A total of 469 different clinical specimens were processed according to the standard methodology. The isolates were identified by standard microbiological procedures and subjected to antimicrobial susceptibility testing by modified Kirby-Bauer disk diffusion method. Production of ESBL was determined by combined disk method.Results: Of the total sample processed, 80 (17.0%) Gram negative bacteria were isolated and 82.5% of them were multidrug resistant (MDR). From the total MDR isolates, 47% were ESBL positive. The higher rate of growth among Intensive Care Units (ICUs) patients was found statistically significant. Higher prevalence of MDR isolates was observed in blood and pus specimens. The majority of the ESBL producers were Escherichia coli (38.7%). Higher rate of ESBL producers was detected from blood (55.6%). Polymyxin B, imipenem and amikacin were the most effective antibiotics against Acinetobacter spp. and Pseudomonas aeruginosa whereas imipenem, amikacin, meropenem were the most effective antibiotics against Enterobacteriaceae.Conclusion: Higher prevalence of ESBL producing MDR Gram negative pathogens in hospitalized patients indicates these bacteria are important health care associated pathogens and requires proper infection control measures that check the transfer of MDR and β-lactamase producing bacterial pathogens among the hospitalized patients.